Produksi Pakan Mandiri Berbahan Tanaman Air Gulma Lahan Basah Bagi Pokdakan Karang Kitri Kota Banjarbaru - Agussyarif Hanafie Hanafie; Akhmad Murjani; Elvina Kartiani (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
Abstract The resulting output target is the Karang Kitri Fish Cultivation Group (Pokdakan), East Landasan Ulin Village, Landasan Ulin District, Banjarbaru City in increasing production of 200 kg / day and quality according to independent feed standards. The solutions offered so that Pokdakan Karang Kitri can increase production and feed quality independently and sustainably are introducing (extension) independent and sustainable feed production and quality techniques and training and demonstration (practice) independent and sustainable production techniques and feed quality. The approach method used is empowerment using stages/steps (preparation, implementation and evaluation); The service activities and stages are detailed as follows: preparation of input materials and tools for the manufacture of fish feed and fish rearing, including: preparation of raw materials for making fish feed, preparation of tools and materials for making fish feed, and preparation of other materials and infrastructure, the process of making feed fish; dispersal of fish seeds into cultivation containers for trial feeding, provision of fish feed to cultured fish, harvesting and evaluation of fish growth and feed manufacturing technology. evaluation and monitoring as well as assistance. The form of evaluation is carried out through evaluation of knowledge and skills (t test) and evaluation of economic value analysis. Results of Statistical Analysis of Hypothesis Testing t-test; t-stat is the t-count value that is equal to 27.61448592. P(T<=t) one tail is a p-value of 4.67292E-27. t critical one tail is the value of t table which is 1.68595446 , or increased from 16% to 70.75% . The results from the manufacture of fish feed are able to produce with a capacity of more than 200 kg/one production and get a price of Rp. 5,450/kg with a feed protein range of 30%. Keywords: production; quality; feed; independent; pokdakan